The Effectiveness of Using Guided Inquiry Based Modules With Concept Cartoon to Minimize Misconceptions in Buffer - Idha Ayu Kusumaningrum Kusumaningrum; Marantika Lia Kristyasari (PT Ilmu Inovasi Nusantara, 2025)
Buffer solutions are a chemistry topic that contains many abstract concepts, calculations, and requires a strong grasp of prerequisite material. The use of inappropriate teaching materials can lead to student misconceptions. This study aims to determine the effectiveness of guided inquiry-based module equipped with concept cartoons in minimizing misconceptions regarding buffer material. This study used an experimental method with a 'Randomized Control Group Pretest-Posttest Design.' The research population consisted of 18 classes of eleventh-grade students from three high schools categorized as high (A), medium (B), and low (C) performance in the Karanganyar Regency. The sample consisted of two classes as the control and experimental groups. Data collection used a testing instrument that had been previously validated by experts. The effectiveness of module was analyzed using a t-test. The results showed that the use of a guided inquiry-based module equipped with concept cartoons was effective in minimizing misconceptions about buffer material. The percentages of misconceptions reduction were 71% for students at SMA A, 56% for students at SMA B, and 52% for students at SMA C. This module is a potential tool for remediation in learning. Concept cartoons in this module can help detect and remediate misconceptions through inquiry.